ASSESSMENT OF CHARACTER EDUCATION IN DARING LEARNING - Aqli, Dana Rosyidal; Musyafa, M Ali (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
The success of the education process is inseparable from how the planning, implementation and assessment or evaluation processes are. Especially at this time during the Covid-19 pandemic where the Government issued a policy on the implementation of online learning, so it needed new and appropriate concepts in the implementation of teaching and learning activities especially in character education assessment as the theme of this paper. The method in this research is descriptive qualitative by collecting data from various references relevant to the observed symptoms, namely the assessment of character education in online learning. This study discusses how the concept of character education assessment in online learning from planning, implementation and management. Character education is a system of naming character values which includes components of knowledge, awareness or willingness, and actions to carry out these values, both towards God Almighty, self, neighbor, environment, and nationality. Online learning, or online, is the translation of the term online which means being connected to a computer network. In conducting affective assessments (attitudes or characters) in online learning apart from educators through observation techniques also through other supporting techniques, namely assessment of parents, individual and peer-to-peer assessments. Other supporting assessments are intended to complement the main assessment, namely observations from educators as additional reference material for the evaluation results process notes, because those who know the shape of a person's original character are the individual himself andhis close surroundings, where in this online learning the parents are the most close to students.